A study of the compliance of selected barangays in Quezon City to relevant laws and regulations on archives and records management - Juanson, Vivian Sarah C.; Buenrostro, Iyra S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
This study was conducted to find out the extent of compliance of the 14 out of 15 selected barangays in Quezon City to the relevant laws, rules and regulations on archives and records management. The following specific objectives were: 1) to determine how many barangays have separate archives and records offices, existing archival systems, policies and practices on archives and records management; 2) to find out the practices of the barangays regarding records storage and maintenance; 3) to know the policies and practices of the barangays regarding the disposal of different barangay records; 4) to determine how many barangays have Records Officers, their responsibilities, duties and practices on archives and records management and to find out the responsibilities and duties of the barangay secretaries, Treasurers and Heads regarding archives and records management and; 5) to come up with recommendations that will improve the existing status of archives and records management of the barangays and their compliance with the laws and regulations.
The respondents were the officers-in-charge of records management in barangays Bahay Toro, Batasan Hills, Culiat, ESCOPA I, Kalusugan, Katipunan, Marilag, Milagrosa, Obrero, Paraiso, Pinyahan, Sangandaan, Socorro and Teachers' Village West. Barangay St. Peter did not participate in the study. Distribution of survey questionnaires and follow-up interviews were done to gather data.
The findings of the study revealed the following: 1) none of the barangays have an existing archival system; 2) most of the barangays' policies on archives and records management are not formally written; 3) only three barangays have centralized receiving and releasing units; 4) only nine barangays have mini-archives; 5) none dispose public and protected records; 6) only eight barangays have Records Officers and; 7) barangay officials are more aware of the laws stated in the Local Government Code of the Philippines or Republic Act No. 7160 compared to the National Archives of the Philippines Act of 2007 or Republic Act No. 9470.
Based on these findings, the study concluded that there is a great and urgent need for the barangays in Quezon City to upgrade and standardize their archives and records management systems in accordance with the Republic Acts and DECS Orders to better serve their constituencies. There is also a need to coordinate with the proper government office, like the National Archives of the Philippines (NAP) to ensure that their archives and records management systems are in accordance with the relevant laws and regulations.
It is therefore recommended that the head of the barangays be required to attend meetings informing them of the need and importance of establishing formal records offices in their barangays; that the Executive Director (ED) of the NAP visit and inspect barangay archives and records units and prepare and implement programs for seminars and training sessions for Records Officers and Custodians of barangays and; that the NAP authority may institute programs to inspire the barangay Records Officers to do their best in complying with the Republic Acts and DECS Orders by giving them awards and recognitions.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Archives -- Law and legislation -- Philippines -- Quezon City; Records -- Management; Local government -- Philippines -- Quezon City